1998
DOI: 10.1007/s001130050256
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis and instrumented measurement of anterior knee laxity. A comparative study of the Lachman test, KT 1000 knee ligament arthrometer and the sonographic Lachman test

Abstract: We reviewed 45 patients on average 14.7 years after surgery for rupture of the anterior cruciate ligament. The aim of the study was to compare the reliability of the Lachman test to evaluation of knee laxity with the KT 1000 arthrometer and the ultrasound-assisted Lachman test. Forty-five knees were examined with the Lachman test: 12 knees showed no sign of instability; 20 had a + positive Lachman test with a hard end point; 6 with a + positive test had no end point and were rated as unstable; a +2 Lachman tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…45,62,67 Eight additional studies did not fulfill the inclusion criteria. 21,25,37,41,43,46,65,66 One study, 55 that was not indexed in 1 of the databases but was identified through personal communication, was added to the included studies. Two articles pertained to the same study.…”
Section: Methodological Quality and Study Characteristicsmentioning
confidence: 99%
“…45,62,67 Eight additional studies did not fulfill the inclusion criteria. 21,25,37,41,43,46,65,66 One study, 55 that was not indexed in 1 of the databases but was identified through personal communication, was added to the included studies. Two articles pertained to the same study.…”
Section: Methodological Quality and Study Characteristicsmentioning
confidence: 99%
“…The objective measurement of sagittal laxity of the knee is imperative for scientific comparisons of the results of anterior cruciate ligament (ACL) surgery. The most commonly used tools are the KT-1000, KT-2000 (MEDmetric, San Diego, Calif., USA), and the Stryker knee laxity testers [1,5,12,14,19]. The diagnostic efficiency of these devices has been confirmed in several investigations [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic ultrasonography overcomes the limitations of needing to directly visualize the entirety of the ACL by indirectly measuring its function. Previous literature has described several dynamic ultrasound variations for assessing ACL integrity by measuring tibial translation relative to the femur (10,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The primary differences among these techniques are patient positioning (prone or supine), transducer placement (anterior or posterior), and force application method (manual, gravity-induced, or device-generated).…”
Section: Summary Of the Previous Literature Regarding Ultrasound For ...mentioning
confidence: 99%
“…In contrast to MRI, musculoskeletal ultrasound (MSKUS) is more cost-effective, portable, and offers the ability to image structures dynamically. As the use of MSKUS has become more prevalent, an increasing number of studies have documented the efficacy of using this modality to diagnose ACL tears (10–12,14–36). However, tremendous heterogeneity exists between approaches, and optimal technique has not been clearly described in the literature.…”
Section: Introductionmentioning
confidence: 99%